A new species of Lathrobium Gravenhorst (Coleoptera: Staphylinidae: Paederinae) from Yulongxueshan Mountain, Southwest China - Peng, Zhong; Li, Li-Zhen; Zhao, Mei-Jun (Zootaxa, 2012)
Up to today, eighteen species of the genus Lathrobium Gravenhorst, 1802 have been recorded from Yunnan Province (Assing, 2012; Bernhauer, 1938; Herman, 2003; Hua, 2002; Watanabe & Xiao, 1994, 1996, 1997, 2000), three of which, L. lijiangense Watanabe & Xiao, 1997, L. yinae Watanabe & Xiao, 1997 and L. naxii Watanabe & Xiao, 1996, are distributed in the Yulongxueshan.